Ex oleo bellare? The Impact of Oil on the Outbreak of Militarized Interstate Disputes - Georg Strüver; Tim Wegenast (German Institute of Global and Area Studies (GIGA), 2011)
According to conventional wisdom, strategic natural resources like oil are harmful to international peace. Nonetheless, there is little empirical quantitative work on the link between resource abundance and interstate conflicts. Analyzing the impact of oil on militarized interstate disputes on a monadic level of analysis, this paper shows that oil in fact influences the conflict potential between countries. Results of logistic regressions suggest that a high absolute oil production is associated with an increased risk of dispute initiation. Per capita oil production, in contrast, does not seem to influence a country's propensity to start militarized conflicts. We also find that while very small oil-rich countries are more frequently the object of military actions, large oil producers seem to be generally spared from foreign attacks. We conclude that specific causal mechanisms such as an increased military capacity or the indulgence of the international community (rather than domestic political conditions inherent to the rentier state) might be particularly useful to explain our findings.
Keywords: F51; Q34; 300; oil; militarized interstate disputes; international conflicts; natural resources; Erdölvorkommen; Politischer Konflikt; Erdölförderung; Rüstungspolitik; Welt